Research progress of peroxiredoxin gene in crustaceans - LI Hui; FENG Wei; YU Junjie; ZHANG Mingyin; ZHOU Chunmiao; TANG Yongkai (浙江大学学报. 农业与生命科学版, 2021)
Peroxiredoxin (Prx) belongs to the superfamily of antioxidant proteins, which widely exists in eukaryotes and prokaryotes, and plays an important role in innate immunity. At present, there are a few researches on the Prx genes in crustaceans, and only partial subtypes of the Prx genes are cloned, and the antioxidant effect is studied only in terms of biological function. In this study, the cloning, phylogeny, tissue expression and biological functions of crustacean Prx genes in recent years were reviewed. Furthermore, researches on Prx genes in crustaceans were prospected, which would provide references for the researches on the structures and biological functions of Prx genes in crustaceans.